1977
DOI: 10.1128/aac.11.6.946
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Influenza Virus Ribonucleic Acid Polymerase by Ribavirin Triphosphate

Abstract: Ribavirin 5′-triphosphate (RTP), derived from the broad-spectrum antiviral compound ribavirin (Virazole), can selectively inhibit influenza virus ribonucleic acid polymerase in a cell-free assay. Ribavirin and its 5′-monophosphate have no effect on the polymerase. The inhibition is competitive with respect to adenosine 5′-triphosphate and guanosine 5′-triphosphate. RTP also inhibits ApG- and GpC-stimulated influenza virus ribonucleic acid polymerase. Since ribavirin is phosphorylated in the cell, the inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
156
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(163 citation statements)
references
References 20 publications
5
156
0
2
Order By: Relevance
“…24) Furthermore, Eriksson et al found that ribavirin triphosphate, a cellular metabolite of ribavirin, selectively inhibits influenza virus RNA-dependent RNA polymerase. 25) We examined the effect of ribavirin on influenza virus replication in chorion and amnion cells. Virus yields in culture supernatants from both cell types increased about 300-fold in the absence of ribavirin, but increased only 3-or 4-fold at a concentration of 1 mM ribavirin (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…24) Furthermore, Eriksson et al found that ribavirin triphosphate, a cellular metabolite of ribavirin, selectively inhibits influenza virus RNA-dependent RNA polymerase. 25) We examined the effect of ribavirin on influenza virus replication in chorion and amnion cells. Virus yields in culture supernatants from both cell types increased about 300-fold in the absence of ribavirin, but increased only 3-or 4-fold at a concentration of 1 mM ribavirin (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Ribavirin has also been shown to have an inhibitory effect on viral polymerases (9,10). It has been suggested that ribavirin triphosphate could bind to the nucleotide-binding site of polymerases, thereby competitively inhibiting the binding of the nucleotides (11).…”
mentioning
confidence: 99%
“…In fact, it has been shown that ribavirin inhibits influenza virus infection ex vivo and in vivo by inhibition of the viral polymerase (15,50). Through in vitro assays, the influenza A virus infection is inhibited by RTP but is not inhibited by RMP or by nonphosphorylated ribavirin (15).…”
Section: Discussionmentioning
confidence: 99%
“…Ribavirin has proven to be an inhibitor of several ortho-and paramyxoviruses (42). Furthermore, ribavirin inhibits in vitro and in vivo replication of influenza virus (15,33,49,50), the most typical member of the Orthomyxoviridae family.…”
mentioning
confidence: 99%
See 1 more Smart Citation